Ethylene Exerts Species-Specific and Age-Dependent Control of Photosynthesis. Issue 4 (2nd February 2018) - Ceusters, Johan; Van de Poel, Bram
Abstract : Ethylene regulates many different aspects of photosynthesis in an age-dependent and species-specific manner.